Development of Student Worksheets Oriented to Problem Based Learning Integrated 21st Century Skills - Viki Masruroh; Restu Lusiana; Vera Dewi Susanti (STAI Hubbulwathan Duri, 2023)
The results of interviews and observations at the MA Pertanian of Madiun City show that the student worksheet used so far has not integrated 21st century skills. The development of 21st century skills of students can be done through student worksheets that integrate 21st century skills and the use of problem-based learning models. Analysis of these problems and potentials became the basis for researchers to carry out research on the development of problem-based learning-oriented worksheets integrated 21st century skills. This study aims to determine the validity, practicality, and effectiveness of problem-based learning-oriented student worksheets integrated 21st century skills. This development research uses the ADDIE model to achieve research purposes. The ADDIE model consists of 5 stages, namely the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The subjects in this study were 11th grade students of the MA Pertanian of Madiun City in the even semester of the 2021/2022 academic year. The research subjects consisted of 2 types, namely, limited trial subjects and field trial subjects. The research instruments include material expert validation sheets, media expert validation, student response questionnaires, and learning outcomes tests. The results of this study are that the developed student worksheets meet the valid, practical, and effective criteria, so based on the research results it can be concluded that the developed student worksheets are feasible and appropriate to improve students' 21st century skills.